ELECTRICAL PERFORMANCE AND ORGANIC LOAD REDUCTION OF A SYNTHETIC SLUDGE-WASTEWATER MIXTURE FROM A MICROBIAL FUEL CELL - Arteaga Benavides, Beatriz Elizabeth
The objective of this work was to evaluate the electrical performance and the organic load reduction of a Microbial Fuel Cell (MFC), using synthetic wastewater and anaerobic sludge from an area of Túquerres, Nariño. The methodology consisted of determining the electrical performance from the power density and the coulombic efficiency, the decrease of the organic load was determined with the chemical oxygen demand from an estimation and mathematical modeling.The results of this research generated a smallscale electric current with a power density of 875 nW/m2 and an organic matter removal of 97.3%. In conclusion, MCC is an attractive system for electricity generation and organic matter removal that, together with mathematical simulation, would help to predict and calibrate these models for use in future industrial applications.